The Programme for Global Paediatric Research. Issue 7 (21st June 2005) - Manley, M; Zipursky, A
Abstract : Millions of children die every year from malaria, tuberculosis, diarrhoea, neonatal disorders, and many other diseases found primarily in low and mid income countries. Many devoted clinicians and scientists have contributed significantly to the understanding and care of these diseases, however research remains disproportionately aimed at diseases affecting those in high income countries.